PENGARUH UKURAN PERUSAHAAN, ANAK PERUSAHAAN, LEVERAGE DAN UKURAN KAP TERHADAP AUDIT DELAY - Puspitasari, Ketut Dian; Latrini, Made Yeni (E-Jurnal Akuntansi; Vol 8 No 2 (2014), 2014)
Audit delay is the time span of completion of the audit of annual financial statements, measured by the length of days required to obtain an audit report of the independent auditors the annual financial statements of the company, from the date of the closing of the company as of the date indicated on the independent auditor's report. Factors that affect audit delay consideration is the size of the company, subsidiaries, leverage, size of audit firm. The selection of the sample used in this study is purposive sampling with a sample size of 50 companies acquired during the period 2009-2011. Analysis of data using multiple linear regression analysis. The results showed that the size of the company,the size of audit firm affect audit delay, whereas subsidiaries and leverage does not affect the audit delay.
Keywords: Audit Delay, Company Size, Subsidiaries, Leverage and Size of Audit Firm